Elementos de la responsabilidad social universitaria en la labor de los docentes de la carrera de Pedagogía de la Universidad Politécnica Salesiana – Sede Quito - Vega Sicha, Mónica Alexandra (2015)
This research deals with the study of the elements of University Social Responsibility (RSU) in the work of teachers Career Education at the Salesian University (UPS), whereas lack knowledge on the level of teacher involvement in the RSU, and are training the future professionals in the field of education, so the impact of this race in society is high. This covered the bibliographic and documentary methods. Bibliographic information for the construction of the theoretical framework, and documentary information was collected to define the current state of the UPS in relation to the University Social Responsibility. Additionally the results collected in the survey of University Social Responsibility Raza N., and Loachamín J. (2014), were handled. We found that the University Social Responsibility in the UPS is multidimensional expression (institutional, administrative, faculty, and student) and acts in various fields of action, with the common factor focus on contributing to the betterment of society. The elements identified in the work of teachers in the teaching career are implementing the social approach that can be detached from the curriculum (curricular element); the emphasis on aspects of social responsibility that are not established in the curriculum but are or relatable to the race (extracurricular element); the emphasis on values, ethics and behavior (ethical-moral element); and the emphasis placed on teachers on the involvement and participation in the social problems of the country and the community (social element).